2023
DOI: 10.3389/fpubh.2023.1249216
|View full text |Cite
|
Sign up to set email alerts
|

Functional limitation and happiness among older adults: the multiple mediating role of intergenerational support and intergenerational relationship

Angdi Zhou,
Yiwen Song,
Xinru Li
et al.

Abstract: ObjectivesThis study aimed to investigate the relationship between the functional limitation and happiness among Chinese older people and examined the multiple mediating effects of intergenerational support (instrumental support and financial support) and intergenerational relationship.MethodData was drawn from the Chinese Family Panel Survey (CFPS) 2018 and 2020. Structural equation modeling was adopted to analyze the association among functional limitations, intergenerational support, intergenerational relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Research indicates that the highest rates of limitations in both categories are recorded in groups with low education levels, including those with no formal education, incomplete primary school, or only basic education. These results support previous research that also identified similar connections between low education and increased frequency of functional limitations in older individuals [5,[9][10][11][12][13][21][22][23][24][25][26][27][28][29]. It is clear that education plays a crucial role in maintaining functionality in older age, with higher education providing certain advantages that reduce the risk of walking limitations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Research indicates that the highest rates of limitations in both categories are recorded in groups with low education levels, including those with no formal education, incomplete primary school, or only basic education. These results support previous research that also identified similar connections between low education and increased frequency of functional limitations in older individuals [5,[9][10][11][12][13][21][22][23][24][25][26][27][28][29]. It is clear that education plays a crucial role in maintaining functionality in older age, with higher education providing certain advantages that reduce the risk of walking limitations.…”
Section: Discussionsupporting
confidence: 90%
“…One often noted factor associated with physical activity in older adults is gender, with studies suggesting that women are less inclined towards physical activity compared to men [4,5,[10][11][12][13][21][22][23][24]. Reduced physical activity in women may increase the risk of various health problems, including the more frequent occurrence of chronic diseases and the risk of falls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation